PENERAPAN ALAT PERAGA TANGGA PINTAR PADA PEMBELAJARAN MATEMATIKA MATERI PENJUMLAHAN UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS II SEKOLAH DASAR 186/I SRIDADI - Yoga Andhika Pratama; Faizal Chan; Khoirunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe the increase in student learning activeness using smart ladder props in learning mathematics addition material in elementary school. This research is a type of classroom action research consisting of two cycles, each of which is conducted 2 times a meeting. Each cycle consists of 4 stages, namely (1) action planning, (2) action implementation, (3) observation and (4) reflection. The subjects of this research were grade II students of SDN 186/I Sridadi with 18 students. Data collection in this study was an observation sheet of student learning activeness, teacher activity sheets in each cycle in implementing learning through the application of smart ladder props and documentation. The results of this study indicate that the application of smart ladder props in learning class II mathematics can increase the learning activeness of students. The increase can be seen in the data analysis of each meeting cycle. Cycle I the level of student learning activeness occurred at 44.44%. Then there was an increase in cycle II of 88.88%. Then there was an increase in cycle II of 88.88%. Based on the results of the research that has been carried out, it can be concluded that the application of smart ladder props using the Project Based Learning model is able to increase the learning activeness of students as seen from the percentage increase cycle from cycle I to cycle II so that overall it can be used in the learning process in elementary schools.